Far-Field Super-Resolution Imaging of Scatterers With a Time-Reversal System Aided by a Grating Plate - Zhi-Shuang Gong; Bing-Zhong Wang; Yu Yang; Hong-Cheng Zhou; Shuai Ding; Xiao-Hua Wang (IEEE Photonics Journal)
A time-reversal imaging system for far-field super-resolution imaging of scatterers is proposed. First, a grating plate, similar to the optical far-field super lens, is designed to convert near-field evanescent waves to propagative waves with wavevector modulation. Then, the scattered signals are processed by a time-reversal (TR) technique and retransmitted back. Finally, the images of the targets are reconstructed by doing demodulation operations in the k-domain to the TR field at the refocusing time. Imaging results show that two scatterers separated by 0.1 λ can be distinguished clearly.